Inter-Professionalism in Health Care Post-graduate specialization: an innovative Laboratory - Artioli, Giovanna; Cosentino, Chiara; Foà, Chiara; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Inter- professional Collaboration (IPC) is an important component of a well-functioning healthcare system. It is linked to improvements in patient safety and case management, optimal use of the skills of each healthcare team member and provision of better health services. Inter- professional Education (IPE), is one key factor in the development of positive behaviors useful for IPC: the basic and post-basic training are key moments to raise awareness, train and help implement the IPC. Aim of this paper is to present and evaluate the use of an innovative laboratory of Consensus Conference implemented in the Nursing Post-graduate specialization at the University of Parma to train students to IPC. Methods: An Innovative Laboratory inspired by of the Consensus Conference (CC) methodology on the “Integrated Narrative Nursing Assessment” was designed. Three Post-graduate specialization courses were involved and assigned to different tasks in the CC, according to the characteristics of the specializations. Results: Strengths and weaknesses of the methodology were analyzed. Strengths: students’ engagement in their competencies building, and the acquisition inter-professional collaboration skills. Weaknesses: the lack of time to develop the whole process, and the need of a deeper guidance in the scientific production. Conclusions: Although the methodology have to be continuously improved through practice, this experimental Laboratory reached the aim of offering a real experience of IPC to the students. They really collaborated with different professionals to reach a common goal and being already considered an expert.